Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.gfs.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to maintaining cereal productivity under climate change

Abstract: Journal articleIFPRI3; ISIEPTDP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 65 publications
0
94
0
2
Order By: Relevance
“…Under these conditions, yields of staple cereal crops (e.g. bread wheat [Triticum aestivum], rice [Oryza sativa], and maize [Zea mays]), which provide over 50% of human calories, are predicted to decrease (Reynolds et al, 2016). Thus, elucidating the mechanisms underlying plant-resilience to suboptimal field conditions and developing stress-tolerant crops is the most promising strategy to ensure global food security.…”
mentioning
confidence: 99%
“…Under these conditions, yields of staple cereal crops (e.g. bread wheat [Triticum aestivum], rice [Oryza sativa], and maize [Zea mays]), which provide over 50% of human calories, are predicted to decrease (Reynolds et al, 2016). Thus, elucidating the mechanisms underlying plant-resilience to suboptimal field conditions and developing stress-tolerant crops is the most promising strategy to ensure global food security.…”
mentioning
confidence: 99%
“…We have developed and evaluated a field phenotyping system, and applied it to wheat, a key staple crop [12], and its response to nitrogen deficiency, a major issue for sustainable agriculture [17,19]. We have shown that these technologies can contribute to development of our knowledge base on the crop functions that influence yield and its response to nitrogen, and could help in identifying important genes involved, and contribute to evaluating new wheat genotypes developed for improved photosynthesis [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…The previous phase of massive worldwide yield increases, the so-called "Green Revolution", was underpinned by the joint improvement of crop varieties, through breeding, and of crop management, through intensified agronomy and input use [9,10]. In the current situation, plant breeding will again be a key component to respond to the challenge of increased food production [11,12]. The pace of progress from plant breeding will need to be even quicker than was previously the case, to keep up with the pace of increasing demand [10,13], but also to counterbalance effects of climate change and increasing environmental costs of excess reliance on inputs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the call for more collaborative work is continually made, a more determined approach is needed [10,[81][82][83]. Several studies from India are consistent with outputs from cropping system models [3] that project yield reductions of 10-40% by end of century unless adaption begins now, despite the beneficial effects of increased CO 2 [84][85][86][87].…”
Section: Cereal Productivitymentioning
confidence: 95%